Peel Off Gel Mask containing Green Tea Leaf Extract (Camellia sinesis L) with Antioxidant Activity - Anis Yohana Chaerunisaa; Emma Surachman; Zila Khuzaimah (Indonesian Journal of Pharmaceutics, 2021)
Peel off mask has been very popular and preferred due to its ease in application. Gel base has been preferred for its cold and moist sensation during application. When herbal ingredients such as extract is  introduced into gel formulation, the stability then will become an issue. The aim of the study was to formulate the peel-off mask gels containing green tea leaves extract (Camellia sinensis L.) which effective, stable, and safe to be used. The antioxidant study was conducted by using  Diphenylhydrazylpicryl (DPPH) method. The peel-off mask gel formula were Hidroxypropyl Methylcelulosa (HPMC) as gel base at 0.5% concentration and plasticizer Polyvinyl Alcohol (PVA) at concentration of 12%. Evaluation of peel-off mask gel included observation on pH, viscosity, dispersing power, and drying time during the 90 days of storage at room temperature. The IC50 values of the green tea (Camellia sinensis L.) extract was 5.511 ppm. The concentration of green tea leaves extract in the preparation were 1x IC50 (F1); 2x IC50 (F2)  and 3x IC50 (F3). The result showed that all preparations were stable in the aspect of consistency, color, and odor. Viscosity, drying time and dispersing power remained unchanged after 90 days of storage. The pH value changed, but still in the range of acceptable pH of topical preparations. The results of antioxidant activity study showed that formula F3 (peel-off mask gels with 3 x IC50 of green tea extracts) had the highest antioxidant activity.Keywords: antioxidant, Camellia sinensis L., peel off gel masks, green tea